2021
DOI: 10.1186/s12885-021-08702-x
|View full text |Cite
|
Sign up to set email alerts
|

The epigenetic immunomodulator, HBI-8000, enhances the response and reverses resistance to checkpoint inhibitors

Abstract: Background Treatment with immune checkpoint inhibitors (ICIs) targeting CTLA-4 and the PD-1/PD-L1 axis is effective against many cancer types. However, due in part to unresponsiveness or acquired resistance, not all patients experience a durable response to ICIs. HBI-8000 is a novel, orally bioavailable class I selective histone deacetylase inhibitor that directly modifies antitumor activity by inducing apoptosis, cell cycle arrest, and resensitization to apoptotic stimuli in adult T cell lymph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 76 publications
0
20
0
Order By: Relevance
“…However, recent evidence suggests that HDAC inhibition may have roles in the tumor microenvironment ( Li et al, 2021 ). For instance, it has been shown that HDAC inhibition potentiates immunotherapy responses in CT26 and MC38 tumor models ( Bissonnette et al, 2021 ). Our observations introduce the possibility that HDAC inhibition also contribute type I interferons to activate the immune microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent evidence suggests that HDAC inhibition may have roles in the tumor microenvironment ( Li et al, 2021 ). For instance, it has been shown that HDAC inhibition potentiates immunotherapy responses in CT26 and MC38 tumor models ( Bissonnette et al, 2021 ). Our observations introduce the possibility that HDAC inhibition also contribute type I interferons to activate the immune microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to single agent CPI monotherapy, HBI-8000 significantly inhibited tumor growth when combined with the above antibodies (23). Mechanistic analysis of tumors using nanoString gene expression showed upregulation of genes responsible for dendritic cell activity, natural killer cells, and cytotoxic T cells in HBI-8000 monotherapy and in combination groups (23). Interestingly, expression of this group of genes was downregulated in the anti-PD1 monotherapy group, further confirming role of HBI-8000 in the induction of activity of key components of tumor immunity (23).…”
Section: Combination With Checkpoint Inhibitors In Solid Tumorsmentioning
confidence: 97%
“…MC38, CT26, and A20) to investigate its activity in tumor immunity. Compared to single agent CPI monotherapy, HBI-8000 significantly inhibited tumor growth when combined with the above antibodies (23). Mechanistic analysis of tumors using nanoString gene expression showed upregulation of genes responsible for dendritic cell activity, natural killer cells, and cytotoxic T cells in HBI-8000 monotherapy and in combination groups (23).…”
Section: Combination With Checkpoint Inhibitors In Solid Tumorsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, HBI-8000 is a novel, orally bioavailable class I selective histone deacetylase inhibitor, which directly modifies antitumor activity by inducing apoptosis, cell cycle arrest, and resensitization to apoptotic stimuli in adult T cell lymphoma patients. This compound has been shown to augment the activity of ICIs targeting either PD-1, PD-L1 or CTLA-4, and significantly increase tumor regression [106].…”
Section: Ici Combination With Epigenetic Drugsmentioning
confidence: 99%